Peran Dinamis Asrama Santri dalam Mendorong Pemerolehan Bahasa Arab: Pendekatan Psiko-Sosiolinguistik - Husein, Muhammad Fadhil; Muhammad Jafar Shodiq; Lutfi Hidayah (An Naba, 2025)
This study examines the dynamic role of the boarding school at Pondok Modern Al-Furqon in encouraging Arabic language acquisition through a psycho-sociolinguistic approach. The main issues discussed are how the boarding system supports Arabic language acquisition and the psycho-sociolinguistic factors that influence the students' abilities. This study uses a qualitative method with a descriptive approach, involving observation, in-depth interviews, and analysis of documentation of students' activities. The results of the study indicate that the boarding environment that consistently uses Arabic as the main means of communication contributes significantly to language acquisition. Internal motivational factors, peer support, and the habit of communicating in Arabic are important elements in the acquisition process. In addition, the psycho-sociolinguistic approach highlights the importance of intensive social interaction, especially through informal activities, in accelerating language acquisition. These findings provide new insights into optimizing the boarding environment as an effective means of learning Arabic.